METHODS AIMED AT DEVELOPING ASSOCIATIVE THINKING IN STUDENTS - Zulfiya Nurmakhamatovna Ortikova (Web of Journals Publishing, 2025)
This article explores the concept of associative thinking, its significance in the educational process, and effective methods for developing this type of thinking in students. Associative thinking fosters creativity, rapid and independent expression of ideas among learners. The techniques presented by the author contribute to enhancing students’ communication skills, enriching their vocabulary, and expanding their imagination within classroom settings.
Keywords: Associative thinking, creativity, figurative thinking, methodology, education, students, independent thinking, speech development, vocabulary.